The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1985
DOI: 10.2527/jas1985.614905x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the β-Adrenergic Agonist Cimaterol (CL 263,780) on the Growth and Carcass Characteristics of Finishing Swine

Abstract: A randomized complete-block design was used to evaluate the effects of the beta-adrenergic agonist, cimaterol (CL 263,780), on growth rate, feed efficiency and carcass composition of finishing swine. The drug was fed at four levels (0, .25, .5 and 1.0 ppm) to a total of 240 pigs from 64.5 to 103.7 kg live weight. Growth rate and feed efficiency were measured during the 7-wk feeding trial. Feeding cimaterol depressed feed intake, improved feed efficiency and did not alter rate of gain. Carcass evaluation showed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
46
3
2

Year Published

1987
1987
2012
2012

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 134 publications
(60 citation statements)
references
References 8 publications
8
46
3
2
Order By: Relevance
“…Jones et al (1985) relataram que o uso de agonistas β adrenérgicos nas dietas leva à produção de uma carne suína mais dura. Warris et al (1991), ao compararem os resultados da análise sensorial com a avaliação mecânica da força de cisalhamento, em carne de suínos alimentados com dietas contendo agonistas β adrenérgicos, observaram aumento da força de cisalhamento, porém não detectado pela análise sensorial.…”
Section: Resultsunclassified
“…Jones et al (1985) relataram que o uso de agonistas β adrenérgicos nas dietas leva à produção de uma carne suína mais dura. Warris et al (1991), ao compararem os resultados da análise sensorial com a avaliação mecânica da força de cisalhamento, em carne de suínos alimentados com dietas contendo agonistas β adrenérgicos, observaram aumento da força de cisalhamento, porém não detectado pela análise sensorial.…”
Section: Resultsunclassified
“…chickens (Dalrymple et al 1983;, pigs (Jones et al 1985), lambs Dalrymple et al 1985;Beermann et al 1985b) and steers (Ricks et al 1984). The effects on the carcass lipid content are dramatic and are readily discernible even by a casual visual inspection of the carcass.…”
Section: R E S U L T Smentioning
confidence: 99%
“…Crome et al (1996) reported that ham bone weight as a percentage of the trimmed ham decreased due to ractopamine. Likewise, pigs fed the bAR agonist cimaterol had shorter and lighter femurs compared with control pigs (Jones et al, 1985).…”
Section: Efficiency or Energy And Protein Depositionmentioning
confidence: 89%